Pharmacogenetics of Atremorine-Induced Neuroprotection and Dopamine Response in Parkinsonʼs Disease - Cacabelos, Ramón; Carrera, Iván; Alejo, Ramón; Fernández-Novoa, Lucía; Cacabelos, Pablo; Corzo, Lola; Rodríguez, Susana; Alcaraz, Margarita; Tellado, Iván; Cacabelos, Natalia; Pego, Rocío; Carril, Juan C. (Planta Medica, 2019)
Atremorine is a novel bioproduct with neuroprotective effects on dopaminergic neurons and a natural L-DOPA donor in Parkinsonʼs disease (PD). In the present study, we show the effects of a single dose of Atremorine (5 g, p. o.) on plasma dopamine (DA) response and brain function in PD (n = 183) and the influence that pathogenic (LRRK2), metabolic (CYP2D5, CYP2C9, CYP2C19, CYP3A5, NAT2), transporter (ABCB1), pleiotropic (APOE), and detoxifying genes (CYP1B1, GSTT1, GSTP1, GSTM1, SOD2) involved in the pharmacogenetic network exerts on Atremorine-induced DA response. Over 90% of PD patients at diagnosis show plasma DA levels below 20 pg/mL. Atremorine induces DA synthesis causing a significant increase in plasma DA levels 1 h after administration in practically 100% of patients. Females tend to show lower basal DA levels than males and the response of DA to Atremorine is stronger in males than in females. Atremorine-induced DA response is pharmacogenotype-specific and lasts from 6 – 12 h depending upon the pharmacogenetic profile of each patient. Genetic variants in pathogenic genes, metabolic genes, and genes involved in the detoxification processes affect the response of DA to Atremorine in a genotype-specific manner. Atremorine or any of its bioactive components can cross the blood-brain barrier and improve brain function and motor function, as revealed by the reduction in slow wave activity in brain mapping and psychometric assessment, respectively. Atremorine is a selective neuroprotective agent for dopaminergic neurons with prophylactic and therapeutic potential in PD.
Keywords: atremorine; metabolic genes; pathogenic genes; Parkinsonʼs disease; pharmacogenetics; Vicia faba; leguminosae